The distribution of Amblyomma variegatum and A. hebraeum in Zimbabwe and their infection with Ehrlichia ruminantium and Rickettsia africae - Neves, Luís C.B.G. (University of Pretoria, 2019)
Dissertation (MSc)--University of Pretoria, 2018.